Overloaded Transmission Lines Protection Based On Intelligent Control Protection Scheme - Ali, A.; Abdalla, Ahmed N.; Ruhaizad, Ishak; Jaber, Aqeel S. (Medwell Journals, 2016)
Some significant issue transmission lines protection in areas that have high renewable energy resources penetration especially wind power generation have defied the System Protection Scheme (SPS)designing these days. It is potentially, unavoidable to experience overloading problem during critical contingencies when a specific geographic area gathers around large wind generations. The primary focus of this study rests on creating an intelligent special protection and control scheme which integrates an intelligent strategy. Broadly speaking, the wind farm system stys far from the main center load based on the N-2 contingency indicating the loss of any (line, transformer and generator) seeking to ascertain the operating restrictions in different contexts. To address the issue of transmission lines overloading in high wind generation area for regulating the generation, the load is shed and system configuration changed in a reliable and efficient manner. The rationale for the proposed strategy will be experimented on a standard IEEE test system.